AUTOMATISASI KALIBRASI SENSOR SUHU PTC DAN NTC MEMPERGUNAKAN SUMBER TEGANGAN TERPROGRAM DAC7611 - Herman Syahputra; Lazuardi Umar; Rahmondia Nanda Setiadi (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
A system  calibration  of  PTC  and  NTC  temperature  sensor  using a preprogrammable voltage source based on DAC7611  was  designed.  Temperature  sensors  of  PTC  typethermistor used was a type of  RS  and  NTC  type  was  B57962  S282  using  a  standard voltage divider with resistance to both sensors. Sensor voltage was  increased with a step interval  of 1V  and  time  equilibrium  sensors  of  120  s.  The characteristic  of  the sensor were  modeled  in the form of  the curve  I(U)  based on the  self-heating  effect  (Self-Heating).  Results of  measurements  and  modeling  using  automatic  and  manual calibration  showed  two curves  coincided,  but  there  was  a difference  of  5,8mA maximum  current  for  the PTC  sensor  and  0,552mA  for  NTC  sensor.  These resultsindicated  that the  manufacturing  of  automatic  calibration system  worked  and  only  had  a small difference to the  manual calibration. This was due to the difference in  temperature of the ambient.